BUTIK HS MODISTE YANG MENGGABUNGKAN SENTUHAN HANDMADE DENGAN TREN MODERN - M. Afrizal Miradji; Halimatus Sa’diyah; Maria Louisa Watafuhan; Yogi Kurniawan; Adib Farhan Abqory (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Local boutiques must continue to be unique and have a distinct identity in the very competitive fashion sector. The purpose of this study is to examine how HS Modiste Boutique creates distinctiveness by fusing contemporary, fashionable designs with painstakingly crafted details. Direct observation at the boutique, in-depth interviews with the owner and clients, and the use of questionnaires are all part of the qualitative research. The results show that HS Modiste's dedication to manual crafting techniques and careful material selection produces unique creative value and quality in the marketplace. Additionally, the boutique's adaptability and relevance to current consumer needs are ensured by its capacity to incorporate modern aspects, such as contemporary colors and patterns. Delivering aesthetically pleasing, highly functional clothing that appeals to a variety of consumer groups is the foundation of HS Modiste's success, establishing it as a local company that prioritizes building a resilient and inclusive economy requires data systems, speeding digital integration, and diversifying growth through the industrial, export, and digital sectors. The report suggests a coordinated strategy that combines immediate treatments with long-term structural changes.